Abundance of HPV L1 Intra-Genotype Variants With Capsid Epitopic Modifications Found Within Low- and High-Grade Pap Smears With Potential Implications for Vaccinology - Shen-Gunther, Jane; Cai, Hong; Zhang, Hao; Wang, Yufeng (Frontiers in Genetics, 2019)
Background: The aim of this study was to explore the Human Papillomavirus (HPV) genotype composition and intra-genotype variants within individual samples of low- and high-grade cervical cytology by deep sequencing. Clinical, cytological, sequencing, and functional/structural data were forged into an integrated variant profiling pipeline for the detection of potentially vaccine-resistant genotypes or variants. Methods: Low- and high-grade intraepithelial lesion (LSIL and HSIL) cytology samples with +HPV were subjected to amplicon (L1 gene fragment) sequencing by dideoxy (Sanger) and deep methods. Taxonomic, abundance, diversity, and phylogenetic analyses were conducted to determine HPV genotypes/sub-lineages, relative abundance, species diversity and phylogenetic distances within and between samples. Variant detection and functional analysis of translated L1 amino acid sequences determined structural variations of interest. Results: Pure and mixed HPV infections were common among LSIL (n = 6) and HSIL (n = 6) samples. Taxonomic profiling revealed loss of species richness and gain of dominance by carcinogenic genotypes in HSIL samples. Phylogenetic analysis showed excellent correlation between HPV-type specific genetic distances and carcinogenic potential. For combined LSIL/HSIL samples (n =12), 11 HPV genotypes and 417 mutations were detected: 375 single-nucleotide variants (SNV), 29 insertion/deletion (indel), 12 multi-nucleotide variants (MNV), and 1 replacement variant. The proportion of nonsynonymous mutations was lower for HSIL (0.38) than for LSIL samples (0.51) (p<0.05). HPV variant analysis pinpointed nucleotide-level mutations and amino acid-level structural modifications. Conclusion: HPV L1 intra-host and intra-genotype variants are abundant in LSIL and HSIL samples with potential functional/structural consequences. An integrated multi-omics approach to variant analysis may provide a sensitive and practical means of detecting changes in HPV evolution and dynamics within individuals or populations.